Culture and Explicitness of Persuasion: Linguistic Evidence From a 51-Year Corpus-Based Cross-Cultural Comparison of the United Nations General Debate Speeches Across 55 Countries (1970-2020). (April 2023) - Shen, Lin
The explicitness of expression or persuasion has been a critical subject of study in cross-cultural studies. The majority of cross-cultural comparisons in this respect, however, have been based on questionnaires and surveys. This study seeks to diversify the methods and validate the results with a corpus-based register analytical approach. Based on the United Nations General Debate Corpus (UNGDC) that comprises comparable multi-cultural speeches, a diachronic comparison (1970-2020) is made between the 2518 speeches (altogether 7, 090, 221 tokens) of 55 cultures from the East (East, South, and Southeast Asia) and the West (European Union, North America, and Australia) on the dimension 'explicitness of persuasion', a synthesized variable operationalized with 6 linguistic features, with the register analytical framework of Multi-Dimensional Analysis (MDA). The potential impacts of the political contexts on the cross-cultural gap in persuasion explicitness are tentatively discussed with the case studies on China and the United States. The results reveal significant difference between the exemplars from the East and the West on the overtness of persuasion, and the gap is generally narrowing down over the 51 years. The quantitative results provide political-setting linguistic evidence for the relevant findings of Hall, Hofstede, and Inglehart & Welzel, and the narrowing gap between cultures from the East and the West in the explicitness of expression points to an open and dynamic view of cultures. This study may offer implications for further research on the cultural styles of political persuasion.